Peran Kepemimpinan Perempuan Dalam Meningkatkan Kualitas Pendidikan Di Madrasah Tsanawiyah Al Jam’iyatul Washliyah Pangkalan Berandan - Putri Wulandari, Zulfitri (Pusdikra-Publishing.com, 2022)
This thesis is based on the fact that in almost all parts of the world there are still unequal relations between women and men. The head of the madrasa at MTs Al Jam`iyatul Washliyah P. Berandan proved that women can also be leaders in madrasa institutions, namely being a madrasa head. This study aims to describe: the role of women's leadership in improving the quality of education at MTs Al Jam`iyatul Washliyah P. Berandan. This research was conducted at MTs Al Jam`iyatul Washliyah P. Berandan. The approach in this research is descriptive qualitative. The informants in this study were the head of the madrasa, the deputy head of the madrasa in the field of curriculum, teachers and students. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis was carried out by collecting data, reducing data, presenting data and drawing conclusions. Meanwhile, the validity of the data was tested by means of triangulation of sources, triangulation of techniques and triangulation of time. The findings of this study indicate that: 1). The madrasa principal's leadership model applied is transformational leadership. 2). Teacher empowerment carried out by madrasa principals in improving the quality of education is by: a). Participate in training and education and training, b). Provide compensation to teachers who get assignments from the madrasa principal. 3). Supporting factors for madrasa heads in improving the quality of education are formal and informal activities, mutual cooperation and kinship. While the inhibiting factors for madrasa heads in improving the quality of education are facilities and infrastructure.